Cognition and intelligence : identifying the mechanisms of the mind - Sternberg, Robert J.; Pretz, Jean E. (Cambridge ; New York : Cambridge University Press, 2005)
In 1957, Lee Cronbach called on the membership of the American Psychological Association to bring together experimental and differential approaches to the study of cognition. The field of intelligence research is an example of a response to that call, and Cognition and Intelligence: Identifying the Mechanisms of Mind investigates the progress of this research program in the literature of the past several decades. With contributions from formative experts in the field, including Earl Hunt and Robert Sternberg, this volume reviews the research on the study of intelligence from diverse cognitive approaches, from the most bottom-up to the most top-down. The authors present their findings on the underlying cognitive aspects of intelligence based on their studies of neuroscience, reaction time, artificial intelligence, problem solving, metacognition, and development. The book summarizes and synthesizes the literature reviewed and makes recommendations for the pursuit of future research in the field.
Ch. 1. Information processing and intelligence: where we are and where we are going / Earl Hunt -- Ch. 2. Mental chronometry and the unification of differential psychology / Arthur Jensen -- Ch. 3. Reductionism vs charting: ways of examining the role of lower-order cognitive processes in intelligence / Lazar Stankov -- Ch. 4. Basic information processing and the psychophysiology of intelligence / Aljoscha Neubauer and Andreas Fink -- Ch. 5. The neural bases of intelligence: a perspective based on functional neuroimaging / Sharlene D. Newman and Marcel Adam Just -- Ch. 6. The role of working memory in higher-level cognition domain specific vs domain-general perspectives / David Z. Hambrick, Michael J. Kane and Randall Engle -- Ch. 7. Higher-order cognition and intelligence / Edward Necka and Jaroslaw Orzechowski -- Ch. 8. Ability determinants of individual differences in skilled performance / Phillip Ackerman -- Ch. 9. Complex problem solving and intelligence: empirical relation and causal direction / Dorit Wenke, Peter A. Frensch and Joachim Funke -- Ch. 10. Intelligence as smart heuristics / Markus Raab and Gerd Gigerenzer -- Ch. 11. The role of transferable knowledge in intelligence / Susan Barnett, Stephen J. Ceci and Hwakin Yan -- Ch. 12. Reasoning abilities / David Lohman -- Ch. 13. Measuring human intelligence with artificial intelligence: adaptive item generation / Susan Embretson -- Ch. 14. Marrying intelligence and cognition: a developmental view / Mike Anderson -- Ch. 15. From description to explanation in cognitive aging / Timothy A. Salthouse -- Ch. 16. Unifying the field: cognition and intelligence / Jean Pretz and Robert J. Sternberg --
Includes bibliographical references (p. 318) and indexes.
Keywords: Cognition; Intellect; Cognitive psychology